Analisis Pengaturan Quarter-Car Active Suspension Menggunakan Neuro-Fuzzy Adaptif PID Control - Ferdinandus, Aprildy Randy Andrew; Bumbungan, Santo Junital (Jurnal Fokus Elektroda : Energi Listrik, Telekomunikasi, Komputer, Elektronika dan Kendali), 2021)
Car as a vehicle has a suspension on the wheels that connect the body with the road surface. The suspension is arranged in such way as to ensure the comfort in driving even on uneven road surfaces or damaged road surfaces. Because of the changes in road surface, it is very important to make adjustments to the suspension. The car suspension is adjusted using Neuro-Fuzzy Adaptive PID Control System so that the performance of the suspension can be improved in ensuring user comfort by reducing vibrations in the car body. Improved performance can be seen in the results of the suspension setting, which can suppress the movement of the car body because of the change in road surface more than 80%.